Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1099/00222615-48-10-917
|View full text |Cite
|
Sign up to set email alerts
|

Colostral proteins from cows immunised with Streptococcus mutans/S. sobrinus support the phagocytosis and killing of mutans streptococci by human leucocytes

Abstract: Passive immunisation, based on bovine colostral preparations, is an area of active research. Specific bovine antibodies inhibit the virulence factors of target pathogens but the interactions between whey preparations and human immune defence cells are not well known. Bovine colostrum inhibits the phagocytic activity of bovine leucocytes and this may reflect the biological activity of immunoglobulins in it. Therefore, this study aimed to examine the effects of bovine whey protein preparations from the colostrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
0
19
1
1
Order By: Relevance
“…It has been shown that certain probiotic bacteria and triherbal extracts are able to stimulate phagocytic activity (Arunachalam et al 2000, Schiffrin et al 1997, Harikrishnan et al 2009) as well as complement receptor expression (Pelto et al 1998). Respiratory burst activity correlates well with phagocytosis of bacteria in fish (Hardie et al 1996, Neumann et al 2001 as well as in humans (Loimaranta et al 1999). The chemiluminescence-based respiratory burst assay is, therefore, a rapid method for analysing phagocytic activity (Lilius & Waris 1984).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that certain probiotic bacteria and triherbal extracts are able to stimulate phagocytic activity (Arunachalam et al 2000, Schiffrin et al 1997, Harikrishnan et al 2009) as well as complement receptor expression (Pelto et al 1998). Respiratory burst activity correlates well with phagocytosis of bacteria in fish (Hardie et al 1996, Neumann et al 2001 as well as in humans (Loimaranta et al 1999). The chemiluminescence-based respiratory burst assay is, therefore, a rapid method for analysing phagocytic activity (Lilius & Waris 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Since H. felis does not adhere to murine gastric cells, it is likely that antibodies interfere with motility and/or adhesion to mucus (4). Alternatively, colostral phagocytes might facilitate the clearance of H. felis by internalizing and degrading secretory IgA-opsonized bacteria as reported for enteropathogenic Escherichia coli in infected newborns (13). Whether milk phagocytes express the recently discovered Fc ␣/ receptor (17) and whether such a mechanism plays a role in the clearance of Helicobacter in mouse pups remain to be documented.…”
Section: Vol 71 2003mentioning
confidence: 99%
“…In humans certain probiotic bacteria are able to stimulate phagocytic activity [45] and complement receptor expression [46]. The respiratory activity correlates well with phagocytosis of bacteria in fish [47e49] as well as in humans [49]. In our experiments a high enriched Zooshikella in the diet was able to significantly enhance the phagocytic activity of leukocytes in infected olive flounder only after 4th week.…”
Section: Discussionmentioning
confidence: 79%